32. DESCRIPTION OF THE EPIDEMIOLOGICAL CHARACTERISTICS OF COVID-19 AND THE CAPACITY TO TRACK CLOSE CONTACTS OF THE DISEASE IN VAN DON DISTRICT, DONG TRIEU TOWN, QUANG NINH PROVINCE IN 2021 (Vietnam Journal of Community Medicine, 2025)
COVID-19 is a ”group A infectious disease” caused by the SARS-CoV-2 virus, first discovered in Wuhan in December 2019. The World Health Organization announced COVID-19 as a global pandemic on March 31, 2020. Tracking, tracing and quarantine are key measures in preventing Covid-19 in the early stages of the epidemic. In January 2021, Quang Ninh recorded 2 Covid-19 outbreaks in Van Don and Dong Trieu districts. Starting from Van Don airport security staff and Poyul company workers in Hai Duong - bordering Dong Trieu. The study describes 61 cases in 2 outbreaks: patients are mainly aged 18-40, accounting for 65.6%. 80.4% of cases have no initial symptoms. There were no severe cases or deaths. Infection is mainly in the work and study environment 42.6% and family 34.4%. 87% of the human resources participating in the search are medical staff. Coordinated contact tracing both in person and indirectly by phone is common. The biggest difficulty in tracing is that the patient does not remember all the contact schedules and does not cooperate. The search will be more effective when there is the participation of units such as the police force and people who understand the customs and culture of each locality.
Keywords: COVID-19; COVID-19 surveillance and prevention system; tracing; epidemiological investigation; close contacts